Actualization of basic knowledge of students in the study subject "Тhe first aid - Zhabotynska, N. V.; Kyreev, I. V.; Peremot, S. D. (Problems of Engineer-Pedagogical Education, 2018)
The requirement of the system of learning and failure set bonds between disciplines and topics account the psychological and socio-demographic characteristics of students, the available material and technical base to form a contradiction, which makes the existence of the problem of improving teaching "The first aid" to students of the National University of Pharmacy. The aim of the study was to develop a theoretical basis and methodology of actualization of basic knowledge of students in the process of studying the discipline "The first aid". The peculiarity of the developed model was the fact that the choice of technology affects not only the content of this new topic, and demands the formation of a system of knowledge that take into account the content and basic training. According to the results of the experiment, it was found increasing academic performance of students and the teacher received the necessary information about the contingent of students, which allowed him to perform most effectively set learning objectives. Implementation of the developed technique will improve teaching in the educational process of discipline "The first aid".